Inequitable Impacts of Textbook Costs at a Small, Private College: Results from a Textbook Survey at Gettysburg College - Sarah Appedu; Mary Elmquist; Janelle Wertzberger; Sharon Birch (Open Praxis, 2021)
Recognizing that higher education settings vary considerably, librarians at Gettysburg College sought to better understand textbook spending behaviors and the effects of costs on our students. We adapted the Florida Virtual Campus 2016 Student Textbook and Course Materials Survey to suit the context of our small, private, liberal arts college. Most students spent $300 in Fall 2019. Financial aid awards did not cover the cost of required books and course materials for most students receiving aid. Negative effects were more pronounced for first-generation students and Pell Grant recipients, who were more likely to not purchase required books, to not register for a course due to cost, and to struggle academically. Some reported negative effects beyond their academic lives, as well. We recommend adoption of Open Educational Resources as an equity-minded practice that addresses this academic success barrier.